2022
DOI: 10.1007/s10902-022-00603-5
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Consumer Confidence and Subjective Well-being on Consumers’ Spending Behavior

Abstract: The paper focuses on the role of consumer confidence and selected well-being measures in aggregate consumption and in subsets of aggregate consumption on a broad set of 22 OECD countries. Consumer confidence played a positive and statistically significant role in the development of expenditures especially on durable and semi-durable goods and services. The increase in cognitive, affective and eudaimonic measures of well-being, measured by the Cantril ladder, positive and negative affect and freedom to make lif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 186 publications
0
3
0
Order By: Relevance
“…Our research direction was very similar and the findings confirm the points stated below. Supplementary Table S4 and global research have shown that some areas need to be explored more, such as better gender equality 69 , corruption 70 reduction, emphasis on human development 71 , advances in democracy 72 , and happiness 73 . Such research emphasizes social 74 , 75 and cultural 76 , 77 factors, as well as supporting our regression and MCDM analysis results, which prove our first hypothesis that improvements in climate change indicators and mitigation, adaptation, and resilience actions can be achieved for countries and cities considered without sticking just to environmental, economic, and other traditional means (Supplementary Table S4 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our research direction was very similar and the findings confirm the points stated below. Supplementary Table S4 and global research have shown that some areas need to be explored more, such as better gender equality 69 , corruption 70 reduction, emphasis on human development 71 , advances in democracy 72 , and happiness 73 . Such research emphasizes social 74 , 75 and cultural 76 , 77 factors, as well as supporting our regression and MCDM analysis results, which prove our first hypothesis that improvements in climate change indicators and mitigation, adaptation, and resilience actions can be achieved for countries and cities considered without sticking just to environmental, economic, and other traditional means (Supplementary Table S4 ).…”
Section: Discussionmentioning
confidence: 99%
“…Consumer confidence, fueled by economic stability, serves as a driving force behind this phenomenon. Notably, it plays a significant and positive role in stimulating expenditures, particularly for durable and semi-durable goods as well as services, as highlighted by [39]. Furthermore, embracing positive uncertainty can facilitate the integration of novel types of goods and services, paving the way for implementing innovative ideas, capabilities, and skills.…”
Section: Consumption Expenditure and Gdpmentioning
confidence: 99%
“…Consumer confidence, fueled by economic stability, serves as a driving force behind this phenomenon. Notably, it plays a significant and positive role in stimulating expenditures, particularly for durable and semidurable goods as well as services, as highlighted by [39]. Furthermore, embracing positive uncertainty can facilitate the integration of novel types of goods and services, paving the way for implementing innovative ideas, capabilities, and skills.…”
Section: ) the Study Also Reveals That Public Consumption Complements...mentioning
confidence: 99%